If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = 2x + 21 Reorder the terms: 9 + 5x = 2x + 21 Reorder the terms: 9 + 5x = 21 + 2x Solving 9 + 5x = 21 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 5x + -2x = 21 + 2x + -2x Combine like terms: 5x + -2x = 3x 9 + 3x = 21 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + 3x = 21 + 0 9 + 3x = 21 Add '-9' to each side of the equation. 9 + -9 + 3x = 21 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 21 + -9 3x = 21 + -9 Combine like terms: 21 + -9 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 6m+2p-4m+3p= | | 14a-93=49-57u | | 5x-10=10x-5 | | 2p-5=19-p | | 5x+(3x+12)=180 | | 4X-8=3X-5 | | 3x-30=x+10 | | 9.8-5p=4p-1 | | x+.5x=10 | | 4x-6=2+12x | | K^2+16=0 | | 10x-1=8x+21 | | -2(3-x)=4x+10 | | -4(-1+7b)+2b=-100 | | 4x+3=2+6x | | A=3a-2b-4c | | K^2+6k+9=0 | | 10y-8=4-6y | | 3(2x-1)+4(3x-2)= | | (-5*-5+8-3)/3+6= | | (-5x-5+8-3)/3+6= | | 2w^2-3w=0 | | 2x+10=62-7x | | 3x-14+4x-22=90 | | 5(2d+8)=2(3d+24) | | f=ma+b | | 9a^2-(3a-2b)(3a-2b)=0 | | 15x+19=5x+239 | | 3x+2=-1x+3 | | x^3+8x-4x^2=0 | | x^3+8x^2-4x=0 | | 8s-4(2s+3)= |